PEMAHAMAN MAHASISWA TERHADAP BEBERAPA TERMINOLOGI AKUNTANSI - Anggon ,; Sofyan S. Harahap; Ramlan Harahap (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2006)
The paper studies how far the understanding of students on ten accounting terrminologies e.i.: (1) cost, (2) expense, (3) revenue, (4) income (5) inventory, (6) gain, (7) loss, (8) depreciation, (9) retained earning, and 10) going concern. The study is conducted in a private university on each department: accounting, management and economics on the academic year 2003/2004. The respondents were in the sixth or seventh semester, intake, 2001, 2000, 1999 and before. Samples of 150 are selected by using convenience probability sampling. F test and ANOVA, Turkey test and Bonferroni were used in every level and propose. The tudy shows that the understanding of the student on those terminologies are vary. The percentage of student's understand correctly the terminologies are (1) cost, 35%, (2) expense, 13% (3) revenue, 37% (4) i come, 30% (5) inventory, 65% (6) gain, 36% (7) loss, 29% (8) depreciation, 25% (9) retained earning, 49% and (10) going concern, 19%.keywords: accounting education, student understanding, accounting terminology.